2018
DOI: 10.1080/19490976.2018.1458180
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid oxidation byEggerthella lentastrains C592 and DSM 2243T

Abstract: Strains of Eggerthella lenta are capable of oxidation-reduction reactions capable of oxidizing and epimerizing bile acid hydroxyl groups. Several genes encoding these enzymes, known as hydroxysteroid dehydrogenases (HSDH) have yet to be identified. It is also uncertain whether the products of E. lenta bile acid metabolism are further metabolized by other members of the gut microbiota. We characterized a novel human fecal isolate identified as E. lenta strain C592. The complete genome of E. lenta strain C592 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
102
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 65 publications
(93 reference statements)
4
102
1
Order By: Relevance
“…We observed genes in both the methyl branch and the carbonyl branch of the Wood-Ljundhal Pathway in the genome of E. lenta DSM 2243. Acetogens require acetyl-CoA synthase/carbon monoxide dehydrogenase, and these genes are located in a gene cluster (Elen_3026-3030) in E. lenta DSM 2243 [75]. We also observed that iso-CDCA is highly resistant to bile acid 7a-dehydroxylation by C. scindens as this bacterium does not have 3b-HSDH.…”
Section: Bile Acid Oxidation By Eggerthella Lentamentioning
confidence: 65%
See 4 more Smart Citations
“…We observed genes in both the methyl branch and the carbonyl branch of the Wood-Ljundhal Pathway in the genome of E. lenta DSM 2243. Acetogens require acetyl-CoA synthase/carbon monoxide dehydrogenase, and these genes are located in a gene cluster (Elen_3026-3030) in E. lenta DSM 2243 [75]. We also observed that iso-CDCA is highly resistant to bile acid 7a-dehydroxylation by C. scindens as this bacterium does not have 3b-HSDH.…”
Section: Bile Acid Oxidation By Eggerthella Lentamentioning
confidence: 65%
“…The identity of genes encoding 7a-HSDH in E. lenta is still unknown, although reported in other gut bacteria such as C. scindens [56], Escherichia coli, and Bacteroides fragilis [47]. Intriguingly, when the gas atmosphere is replaced with hydrogen, bile acid oxidation is dramatically inhibited [75]. Intriguingly, when the gas atmosphere is replaced with hydrogen, bile acid oxidation is dramatically inhibited [75].…”
Section: Bile Acid Oxidation By Eggerthella Lentamentioning
confidence: 99%
See 3 more Smart Citations